THE IMPACT OF COVID-19 ON LABOUR MARKET IN NORTH MACEDONIA - Zulfiu Alili, Merita (Faculty of Economics-Skopje, SS. Cyril and Methodius University in Skopje, 2020)
An initial assessment of the impact of COVID-19 on the North Macedonian labour market is widely anticipated that will be severe, pushing thousands of people into unemployment, underemployment and working poverty. This paper aims to assess the impact of the COVID-19 outbreak on labour market by analysing the most affected sectors and government measured aimed to prevent job losses. Many small and medium businesses have already closed their operations or decreased the number of employees. The most affected industries due to the outbreak of the COVID-19 are the tourism industry and export-oriented industries, including the textile sector. To mitigate the consequences of COVID-19 the Government of North Macedonia has adopted measures for support of the firms which aim to keep jobs, maintain social stability, and help the citizens affected by the crisis. Specific local labour market characteristics should be considered when specifying eligibility criteria and undertaking crisis response measures.
Keywords: COVID-19; labour market; job losses; response measures